Arthropathy, osteolysis, keloids, relapsing conjunctival pannus and gingival overgrowth: A variant of polyfibromatosis?. Issue 6 (1st May 2013) - Cinotti, Elisa; Ferrero, Giulio; Paparo, Francesco; Papadia, Marina; Faravelli, Francesca; Rongioletti, Franco; Traverso, Carlo; Di Maria, Emilio
Abstract Polyfibromatosis is a rare fibrosing condition characterized by fibromatosis in different body areas and by keloid formation, and which can be associated with arthropathy and osteolysis. Familial occurrence has been described, but the cause remains unknown. Here, we describe a patient with characteristics of polyfibromatosis with arthropathy who had in addition severe conjunctival fibrosis, distinctive face, gingival overgrowth, and pigmented keloids. We discuss the resemblances and differences with polyfibromatosis and descriptions of other, similar patients. We conclude that at present it remains uncertain whether the patient has a variant of polyfibromatosis or a separate entity. © 2013 Wiley Periodicals, Inc.